2004
DOI: 10.1016/s0896-6273(04)00069-8
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Promote the Death of Developing Purkinje Cells

Abstract: The loss of neuronal cells, a prominent event in the development of the nervous system, involves regulated triggering of programmed cell death, followed by efficient removal of cell corpses. Professional phagocytes, such as microglia, contribute to the elimination of dead cells. Here we provide evidence that, in addition to their phagocytic activity, microglia promote the death of developing neurons engaged in synaptogenesis. In the developing mouse cerebellum, Purkinje cells die, and 60% of these neurons that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
504
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 656 publications
(522 citation statements)
references
References 75 publications
15
504
2
1
Order By: Relevance
“…Therefore, phagocytic cells labeled in the developing optic nerve may be participating in the clearance of axonal debris of degenerating ganglion cells, as has been proposed for microglia in the postnatal rabbit retina (Schnitzer, 1989) or for activated microglia after optic nerve cut (Thanos et al, 1992;Lawson et al, 1994). Furthermore, during development of other regions of the murine central nervous system, apoptotic neurons and their connections are actively and rapidly removed by microglia (Frade and Barde, 1998;Marin-Teva et al, 2004).…”
Section: Spatiotemporal Distribution Of Cathepsin B/d-expressing Macrmentioning
confidence: 96%
“…Therefore, phagocytic cells labeled in the developing optic nerve may be participating in the clearance of axonal debris of degenerating ganglion cells, as has been proposed for microglia in the postnatal rabbit retina (Schnitzer, 1989) or for activated microglia after optic nerve cut (Thanos et al, 1992;Lawson et al, 1994). Furthermore, during development of other regions of the murine central nervous system, apoptotic neurons and their connections are actively and rapidly removed by microglia (Frade and Barde, 1998;Marin-Teva et al, 2004).…”
Section: Spatiotemporal Distribution Of Cathepsin B/d-expressing Macrmentioning
confidence: 96%
“…Tumor-associated microglia constitute the main population of brain immune cells (Graeber et al, 2002) and are important for monitoring their local environment, regulating function and apoptosis, and secreting proinflammatory cytokines (Banati et al, 1993;Elkabes et al, 1996;Marı´n-Teva et al, 2004;Roumier et al, 2004). These resident brain immune system mononuclear cells can be recruited by glioma tumors cells to the local tumor microenvironment by vascular Figure 3 Co-evolution of neoplastic and non-neoplastic cells in gliomas.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 99%
“…However, further studies will be needed to determine whether the observed Purkinje cell loss is linked to an increased ROS production in Rora +/sg mutants. Furthermore, many studies have proposed the existence of a developmental Purkinje cell death period, occurring around P3 (52)(53)(54)(55)(56). Interestingly, in Rora sg/sg mice, Purkinje cell loss seems to occur during this period (32).…”
Section: Proliferative and Neuroprotective Function Of Rorα In Thmentioning
confidence: 99%